Hand Rejuvenation with Novel Calcium Hydroxyapatite Dermal Filler (Stiim): a Case Report - Kasai, Matheus; Viana, Renata (Brazilian Journal of Case Reports, 2024)
The report investigates hand rejuvenation using a novel dermal filler based on calcium hydroxyapatite. Hands undergo aging due to environmental factors and age-related changes. We present a case report of a patient who received applications of the product on the dorsum of the hand, exhibiting visible improvement in volume and reduced visibility of veins and tendons. Aesthetic evaluation indicates a 'very much improved' outcome, both for the physician and the patient. This report highlights the promising application of the novel dermal filler for hand rejuvenation.